Flow focusing technique to produce PDMS microparticles for blood analogue fluids - Silva, S.F. (2018)
The study of the blood flow behaviour through microchannels is crucial to improve our understanding about blood flow phenomena happening in the human microcirculatory system. However, the difficulties associated with the use of in vitro blood, such as coagulation and sample storage, have promoted the increasing interest to develop fluids with rheological properties similar to real blood [1]. Polydimethysiloxane (PDMS), due its remarkable properties such as good optical transparency, biocompatibility and permeability to gases, is widely used to fabricate microfluidic devices for in vitro blood experiments [2]. Recently, this inert elastomer has been used to produce monodisperse PDMS microbeads through a microfluidic approach [3]. Jiang et. al. have proposed a flow-focusing technique where a PDMS precursor was dispersed into microdroplets within an aqueous continuous phase [3]. By using this method they were able to produce PDMS microbeads with an average dimension of 80 microns. However, to develop blood analogue fluids it is essential to have PDMS microparticles with dimensions more close to the blood cells, i. e., the microparticles should have dimensions smaller than 20 microns. Hence, in this study a novel flow focusing technique was used to produce PDMS microparticles with dimensions more close to real blood cells. This technique was recently proposed to produce jets, droplets, and emulsions with sizes ranging from tens of microns down to the submicrometer scale [4]. This procedure is also based on the flow focusing principle which the above mentioned method relies on. Nevertheless, our technique makes use of the breakage of a steady jet to form the microparticles, which can lead to much higher production rates. In our technique, liquid is injected at a constant flow rate through a hypodermic needle to form a film over the needle’s outer surface. This film flows toward the needle tip until a liquid ligament is steadily ejected. Both the film motion and the liquid ejection are driven by the viscous and pressure forces exerted by a coflowing fluid stream. The outcome is a capillary jet which breaks up into droplets.